Navigating the Digital Learning Era: Computer Vision Syndrome Among Health Science Students - Dewi, Lingga Curnia; Kurniawati, Ninuk Dian; Hidayanti, Rahmalia; Abdullah, Muhammad Rizqy; lestari, Wahyuni Tri; Abdullah, Khatijah Lim (Gaceta Médica de Caracas, 2026)
Introduction: The digital learning era has introduced new challenges to student well-being, particularly concerning visual health. The rapid advancement of online learning enabled by modern digital technologies has led to increased screen time among university students. An initial survey found that a significant number of health science students reported Computer Vision Syndrome (CVS) symptoms due to extended digital learning. This study aimed to analyze factors associated with the severity of CVS.